Cross Laminated Timber : A Design Stage Primer. - Crawley, Nic. (Milton : RIBA Publications, 2021)
Cross-laminated timber (CLT) has long been heralded as a wonder material, with a light environmental footprint, high strength, quick installation times and reduced waste - so why isn't everyone using it? Delving into the key considerations including fire safety, cost and value, visual aspects, planning, feasibility and engineering, this book is an essential companion to designing and delivering exemplar CLT buildings. Abundantly illustrated with over 130 colour images and in-depth case studies from around the world, it will help the entire project team - whether design team, constructor or clients - to better understand and build using a truly modern method of construction. Outlines key challenges as well as benefits of CLT, including quality, cost and environmental benefits, risk reduction and health and safety benefits Presents lessons learnt to aid the development process, from the earliest stages of design to production and assembly Accessible, easy-to-read handbook format allows you to dip in and out, investigating issues as necessary Multidisciplinary in approach with contributions from a range of practitioners
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Laminated wood; Laminated wood construction; ARCHITECTURE / General